Long‐term effectiveness of school‐based children oral hygiene program on oral health after 10‐year follow‐up. Issue 3 (22nd December 2015) - Lai, Hongmin; Fann, Jean Ching‐Yuan; Yen, Amy Ming‐Fang; Chen, Li‐Sheng; Lai, Min‐Hua; Chiu, Sherry Yueh‐Hsia
Abstract: Objective: The aim of this study was to evaluate the long‐term effectiveness of a school‐based child oral hygiene program on oral heath after approximately 10 years of follow‐up. Methods: A prospective cohort study was designed to include 120 schoolchildren aged 10–11 years with instructions on how to practice daily flossing and brushing under the supervision of school nurses for one semester (the intervention group) and to recruit a comparison group with no intervention from 120 classmates matched by gender (the nonintervention group). Both groups participated in a questionnaire survey and received dental examinations after long‐term follow‐up. Results: The mean value of overall plaque score in the intervention group (16.9%) was lower than that of the nonintervention group (32.6%); the adjusted relative risk (aRR) of having a plaque score for the intervention group versus the nonintervention group was 0.4 (95% CI: 0.3, 0.5). The percentage of pocketing (CPI ≧ 2) in the intervention group (75.0%) was lower than that of the nonintervention group (90.8%); the aRR of having calculus or pocketing (CPI ≧ 2) was 0.3 (95% CI: 0.1, 0.6). The intervention group had lower DMFT values and DMFS score than the nonintervention group (4.1 and 6.6 versus 6.2 and 11.0). Moreover, the intervention group had significantly better dental knowledge and habits and dental conditions than the nonintervention group. Conclusions: This longitudinal follow‐up study demonstrated that a highly targeted oral hygiene program can display positive long‐term effectiveness.